Dinamika Kepentingan dan Interaksi Sosial Pedesaan: Studi Implikasi Alih Fungsi Lahan - Dhina Yuliana; Faris Rahmadian; Nana Kristiawan; Selvy Anggriani Syarif (Dinamika Lingkungan Indonesia, 2016)
Land-use changes or land conversion issues not only poses a threat of ecological or environmental, but also trigger a variety of dynamics and complexity of social relations in it. West Cilebut Villages has been the target of investors and developers of housing since the 1990s, and now the West Cilebut Villages has changed from an area full of green “romantic” village, into the region filled with concrete. Therefore, this study was conducted to answer fundamental issues related to the issue of land conversion in the West Cilebut Village, first is to see the map and interests between actors in relation to land conversion in the West Cilebut Village, and second to know the social interactions dynamics that occur in West Cilebut community, following the land conversion from the farm into housing estates. The results showed that there are three main actors in relation to issues of land use change in West Cilebut Village: (1) The Housing Developer; (2) Village Apparatus / Government; (3) Society; where the three actors have a role and importance of different orientations. Meanwhile, social interaction between housing and rural communities basically shows a relationship of mutual need. Construction of housing community that luxurious and exclusive slowly turns into inclusive and reflect a resiprocity of the two communities.